Analisis Sistem Proteksi Petir Pada Menara BTS 42 Meter PT. Telekomunikasi Selular - Dicky Yulvarizal; Iswadi Hasyim Rosma (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Lightning is a natural phenomenon that cannot be controlled or prevented by humans. Lightning strikes not only strike flat areas such as the field, but objects with high structures will be very vulnerable to lightning strikes. Objects that have high-rise structures include trees, housing, skyscrapers, electricity transmission towers, and Base Transceiver Station (BTS) transmitting towers. BTS is a tall building that has a role in the sustainability of data information provision. To prevent the magnitude of the influence of lightning on the information data that is distributed so as not interrupted Lightning Protection System (LPS) is needed. Determination of whether the building requires LPS or not, can be known through several standards, namely the PUIPP standard, NFPA 780 standard and IEC 1024-1-1 standard. In this study, the authors took the 42-meter BTS tower building PT. Telekomunikasi Selular (TELKOMSEL) - Pekanbaru as an object and uses the rolling sphere method as a protection method. Key word: lightning, lightning protection system, BTS, air terminal, down conductor, grounding